Kinetics and Mechanism of Hydrolysis of Mono-p-sulphonic Acid Aniline Phosphate in Acid Media - Shinde, C.P.; Patil (Mhala), R.; Shirdhonkar, Vaishali (Asian Journal of Chemistry, 2010)
Investigation of mono-p-sulphonic acid aniline phosphate was carried out by using "Allen's" modified method of colorimetry, in aqueous medium from 0.1 to 7.0 mol dm–3 HCl at 98ºC. Ionic strength data exhibit different contribution of neutral species and presence of acid catalysis. Theoretical rates estimated from second empirical term of Debye-Hückel equation have been found in close agreement with experimental rates. The effects of ionic strength, temperature, solvent and concentration are provided to identify the reactive species and molecularity. Bimolecular behaviour has been decided by the Arrhenius parameters and by the analysis of molecularity data. The monoester involves P—N bond fission which is strengthened by comparative kinetic data.